Completely-synthesized metal working fluid composite lubricant as well as preparation method and application thereof

By using a combination of PIBSA polyetherester, oleic acid and oleyl alcohol polyoxyethylene ether (10)-maleate in a fully synthesized metal cutting fluid, the problem of reducing lubricating properties and difficult to control foam is solved. Low bubble lubrication and high stability are achieved.

CN119463941APending Publication Date: 2025-02-18NANJING VIROSEC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411368083.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The high water content of the fully synthesized metal cutting fluid reduces its lubricating properties, and in the prior art, polyether esters and self-emulsified esters are prone to form difficult-to-control foams, affecting the stability and application effect of the processing fluid.

Method used

PIBSA polyether ester is used as the main lubricant, combined with oleic acid as the soap-producing agent, and a mixed lubricant is formed by oleic alcohol polyoxyethylene ether (10)-maleate as the dispersant to control foam formation. And improve lubrication performance.

Benefits of technology

It achieves low bubble lubrication effect, improves the thermal storage stability and rust resistance of metal processing liquid, avoids foam overflow problems, and is suitable for water quality conditions in different regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463941A_ABST
    Figure CN119463941A_ABST
Patent Text Reader

Abstract

The invention discloses a total-synthesis metal working fluid composite lubricant as well as a preparation method and application thereof. In the composite lubricant, a main lubricant is PIBSA polyether ester, a dispersing agent is oleyl alcohol polyoxyethylene ether 10-maleate, and a soaping agent is oleic acid; the main lubricant and the dispersing agent are respectively prepared, and are compounded with the soaping agent according to the hard water concentration. The preparation method is simple and feasible, and is suitable for large-scale production; the prepared total-synthesis metal working fluid composite lubricant has a low-foam lubrication effect, has good heat storage stability and anti-rust performance in practical application, and has great industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite lubricant, in particular to a fully synthetic metalworking fluid composite lubricant, and also to a preparation method and application of the fully synthetic metalworking fluid composite lubricant. Background Art

[0002] Fully synthetic cutting fluids are usually composed of lubricants (mainly polyethers, etc.), alcohol amines, isomerized fatty acids, rust inhibitors, bactericides, sedimentation agents, etc. They are currently widely recognized water-based metal cutting fluids with excellent cooling and cleaning properties. These excellent properties are due to the huge advantage of their high water content: in the working fluid, the water content of fully synthetic cutting fluids is generally as high as 95% or more. However, the higher water content also reduces the lubrication performance of fully synthetic metal cutting. The lubrication performance of fully synthetic metal cutting fluids using polyethers and other lubricants is usually weaker than that of semi-synthetic metal cutting fluids. In fully synthetic cutting fluids, the lubricating media are the polyethers and synergistic isomerized fatty acids in the system. The carboxyl groups in the isomerized fatty acids will be adsorbed on the metal surface and lubricate with the polyethers. Although the content of polyethers in cutting fluids is very low, the polyethers themselves will weaken hydrogen bonds as the temperature rises, and then reduce the strength of hydrogen bonds formed by ether bonds, resulting in reduced solubility. The characteristics of precipitation from the system (i.e., the cloud point of the polyethers) cause them to precipitate during the working process, thereby forming an oil film on the surface of the workpiece for lubrication. However, the polyethers themselves are polymers of ethylene oxide and propylene oxide, and the number of carbon hydrocarbon chains they contain cannot be compared with greases. Therefore, their lubricity is generally lower than that of greases, which is the biggest drawback of fully synthetic cutting fluids and the most urgent problem to be solved.

[0003] In order to solve the above problems, the prior art has developed polyether esters and self-emulsifying esters. Polyether esters are a model of lubrication by transplanting the idea of ​​solving lubricity of semi-synthetic liquids into a fully synthetic formula: they have the adsorption of esters in semi-synthetic liquids and the lubricating effect of the oil base, and also have the function of polyether in the fully synthetic liquid to reach the cloud point precipitation, so they have good lubrication effect. However, the core structure of polyether esters and self-emulsifying esters is a product obtained by esterification of polyether and fatty acid. However, since the fatty acid in the polyether ester acts as the oil-based structure, once connected to the polyether, it will be converted into a unit of a non-ionic surfactant similar to a surfactant with an alkane segment on one end and a polyether on the other end, forming difficult-to-control foam.

[0004] For metalworking fluids, soap separation and defoaming are related to each other. The processing fluids have certain requirements for foams, and different processes have different requirements for foams. Generally speaking, stamping processes have low requirements for foams, while processes such as tapping and cutting require the metalworking fluids to be sprayed on the workpiece and tool in the form of high-pressure water flow, which have particularly high requirements for foams, otherwise the foam overflows the tank. The formation of foam is caused by the difference in surface tension. When the surfactant is introduced into the aqueous solution, it will gather at the gas-liquid interface on the liquid surface when it reaches a certain concentration. During the stirring process, the air is entrained to form bubbles due to the hydrophobicity of the lipophilic end. When defoaming, when some insoluble foreign matter is generated on the interface, it will puncture the bubbles, causing the bubbles to burst. Common defoamers such as silicone defoamers usually add fumed silica, which as an insoluble substance will puncture the bubbles and cause defoaming. If fatty acids such as oleic acid are added, fatty acid calcium will be formed in hard water. The ksp of fatty acid calcium is not large and it will usually precipitate. When the amount of soap precipitation is not large and the wetting and dispersion is good, it will pierce the foam as an insoluble matter, thereby causing defoaming. However, this method requires strong skills and formula adaptability, because once too much soap precipitation occurs, a large amount of soap will condense into lumps, which will not only lose the defoaming function but also destroy the stability of the metalworking fluid. Therefore, it is difficult to use controllable soap precipitation to defoam. Therefore, practical metalworking cutting fluids are urgently needed to be developed. Summary of the invention

[0005] Purpose of the invention: The purpose of the present invention is to provide a fully synthetic metalworking fluid composite lubricant that can suppress foam and effectively avoid flocculation through an appropriate amount of soap precipitation, and also to provide a preparation method and application of the above-mentioned fully synthetic metalworking fluid composite lubricant.

[0006] Technical solution: The fully synthetic metalworking fluid composite lubricant of the present invention comprises the following components in percentage by mass: 76% of a main lubricant, 10-14% of a dispersant, and 10-14% of a soaping agent; wherein the main lubricant is polyisobutylene succinic anhydride-polyether ester, the dispersant is oleyl alcohol polyoxyethylene ether 10-maleate, and the soaping agent is oleic acid; the molar ratio of the main lubricant, the dispersant and the soaping agent is 1:0.9-1:1-1.05, preferably 1:1:1.05.

[0007] Wherein, the PIBSA polyetherester is polyetherester 4000 or polyetherester 6000.

[0008] Among them, in the PIBSA polyether ester, both ends of the molecular structure of the polyether ester are terminated with PIBSA carboxyl groups, the carboxyl groups of PIBSA react with polyether to form ester bonds, and the center of the molecular structure is a polyether structure.

[0009] The preparation method of the polyether ester is to esterify the difunctional polyether with polyisobutylene succinic anhydride PIBSA at a temperature of 80°C-90°C for 4-8 hours, using phosphorous acid as the catalyst in an amount of 1.5-3‰, and reacting under the action of nitrogen blowing.

[0010] The difunctional polyether has an EO-PO ratio of 8:2, a molecular weight of 4000-6000, and a molar ratio of polyisobutylene succinic anhydride to the difunctional polyether of 1.85-2.25:1, preferably 2:1.

[0011] Wherein, the oleyl alcohol polyoxyethylene ether 10-maleate is an ester having a carboxyl terminal structure.

[0012] The preparation method of oleyl alcohol polyoxyethylene ether 10-maleate is as follows: esterify oleyl alcohol polyoxyethylene ether 10 with maleic anhydride, with a heating rate of 5-10°C / min, a reaction temperature of 80°C-90°C, nitrogen blowing, a nitrogen flow rate of 250-450mL / min, and a reaction time of 4 hours.

[0013] Wherein, the oleic acid is an unsaturated acid.

[0014] The preparation method of the above-mentioned fully synthetic metalworking fluid composite lubricant comprises the following steps:

[0015] (1) preparing a main lubricant polyisobutylene succinic anhydride-polyether ester;

[0016] (2) preparing dispersant oleyl alcohol polyoxyethylene ether 10-maleate;

[0017] (3) The product is prepared by compounding oleic acid, polyisobutylene succinic anhydride-polyether ester and oleyl alcohol polyoxyethylene ether 10-maleate.

[0018] The above-mentioned fully synthetic metalworking fluid composite lubricant can also be used in the field of metalworking.

[0019] The application is specifically to apply the fully synthetic metalworking fluid obtained by compounding the composite lubricant with an organic solvent and water to metal processing.

[0020] Principle of the invention: The fully synthetic metalworking fluid composite lubricant of the present invention first adopts PIBSA with a molecular weight of 1000 as an aliphatic hydrocarbon chain segment. Since the aliphatic base of the chain segment deviates far from the foaming range of the molecular weight of about 200-250, the intrinsic foam is relatively low. However, if the polyether ester of PIBSA is used alone, in order to balance the water solubility problem of PIBSA, a polyether with a larger molecular weight has to be introduced for solubilization. In order to ensure the freezing point, this part of the polyether has to be embedded with PO, which will further increase the molecular weight of the polyether, and ultimately the product will have a molecular weight of about 6000-8000 while taking into account water solubility, foam and lubricity. Such a huge molecular weight will cause defoaming difficulties. Although the initial foam of the system is limited, it is easy to form residual bubbles and dead bubbles.

[0021] The inventors further discovered that an appropriate amount of soap in the system can effectively suppress foam, but the amount of soap needs to be controlled within a certain range, and effective dispersion is required to avoid flocculation into large particles. Therefore, the fully synthetic metalworking fluid composite lubricant of the present invention is based on PIBSA as an oil-based synthetic polyether ester, and then oleic acid is used as a soaping agent to defoam calcium oleate precipitated in hard water. In order to avoid calcium oleate enrichment and flocculation, the maleate of oleyl alcohol polyoxyethylene ether is used as a dispersant of calcium oleate to form a mixed lubricant. PIBSA polyether ester is used as the main lubricant, and the maleate of oleyl alcohol polyoxyethylene ether (10) is used as a calcium soap wetting and dispersant to break up and disperse the calcium soap, and oleic acid is used as a soaping agent to disperse and wet oleic acid into small particles by using the maleate of oleyl alcohol polyoxyethylene ether (10), suppress the foam of PIBSA polyether ester, and achieve the effect of low-foam lubrication.

[0022] Oleic acid is used as a soaping agent, while oleyl alcohol polyether maleate is used as a wetting and dispersing agent for calcium soap. The essence of this is that the structures of oleyl alcohol and oleic acid are similar, and they can wet and disperse calcium soap to a certain extent. The structure of maleate is anionic in metalworking fluids. The steric hindrance of polyether allows the wetted calcium soap to carry negative charges and large steric hindrance, which hinders the coagulation of calcium soap, thereby forming a wetted and dispersed calcium soap to achieve the function of defoaming. It overcomes the problem of high foam of the main lubricant pibsa polyether ester, and cooperates with the system of controllable calcium soap precipitation to achieve the function of high pb strong lubrication.

[0023] The fully synthetic metalworking fluid composite lubricant of the present invention is applied as a metalworking fluid in the field of metalworking and has strong regional adaptability. When it is diluted and applied on machines in different regions, due to the different water hardness in different regions, when the water quality in some regions is too hard and the calcium content is too high, the soap formed by oleic acid as a soap agent in the composite lubricant will become hard and coagulate, while the dispersant oleyl alcohol polyoxyethylene ether 10-maleate in the composite lubricant can disperse the soap of oleic acid so that it does not agglomerate and achieves a synergistic effect, can defoam, and will not pollute the workpiece and destroy the composition of the processing fluid; ensure that the precipitation of calcium soap is within a reasonable defoaming range and does not generate a large amount of gelled soap; take into account the foam performance and thermal storage stability of the mixture, and carry out anti-rust test, pB test and tapping torque test, which has important application value in practice.

[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) The fully synthetic metalworking fluid composite lubricant of the present invention has a low-foam lubrication effect, and has good thermal storage stability and anti-rust performance in practical applications; (2) The preparation method is simple and easy, suitable for large-scale production, and has good industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The wear spot diagram of the long wear test of the fully synthetic metalworking fluid composite lubricant of Examples 1 to 7;

[0026] Figure 2 The graph is a graph showing the chip anti-corrosion test results of the fully synthetic metalworking fluid composite lubricant of Examples 1 to 7;

[0027] Figure 3 The present invention is a flow chart of the method for preparing the fully synthetic metalworking fluid composite lubricant. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention is further described below in conjunction with the examples. The test materials used in the examples can all be purchased through conventional channels.

[0029] Example 1

[0030] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 76% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0031] The preparation method comprises the following steps:

[0032] (1) A difunctional polyether with a molecular weight of 6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C, a reaction time of 4 hours, phosphorous acid as a catalyst, an addition amount of 3‰, a molar ratio of PIBSA:polyether of 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0033] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0034] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0035] Example 2

[0036] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 7.6% of polyether ester (4000), 68.4% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0037] The preparation method comprises the following steps:

[0038] (1) A difunctional polyether with a molecular weight of 4000-6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid, the addition amount is 3‰, the molar ratio of PIBSA:polyether is 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0039] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0040] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0041] Example 3

[0042] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 22.8% of polyether ester (4000), 53.2% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0043] The preparation method comprises the following steps:

[0044] (1) A difunctional polyether with a molecular weight of 4000-6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid, the addition amount is 3‰, the molar ratio of PIBSA:polyether is 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0045] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0046] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0047] Example 4

[0048] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 38% of polyether ester (4000), 38% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0049] The preparation method comprises the following steps:

[0050] (1) A difunctional polyether with a molecular weight of 4000-6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid, the addition amount is 3‰, the molar ratio of PIBSA:polyether is 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0051] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0052] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0053] Example 5

[0054] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 53.2% of polyether ester (4000), 22.8% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0055] The preparation method comprises the following steps:

[0056] (1) A difunctional polyether with a molecular weight of 4000-6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid, the addition amount is 3‰, the molar ratio of PIBSA:polyether is 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0057] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0058] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0059] Example 6

[0060] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 68.4% of polyether ester (4000), 7.6% of polyether ester (6000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0061] The preparation method comprises the following steps:

[0062] (1) A difunctional polyether with a molecular weight of 4000-6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid, the addition amount is 3‰, the molar ratio of PIBSA:polyether is 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0063] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0064] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0065] Example 7

[0066] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 76% of polyether ester (4000), 12% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 12% of oleic acid.

[0067] The preparation method comprises the following steps:

[0068] (1) A difunctional polyether with a molecular weight of 4000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid in an amount of 3‰. The molar ratio of PIBSA to polyether is 2:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0069] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0070] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0071] Example 8

[0072] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 76% of polyether ester (4000), 10% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 14% of oleic acid.

[0073] The preparation method comprises the following steps:

[0074] (1) A difunctional polyether with a molecular weight of 4000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid in an amount of 3‰. The molar ratio of PIBSA to polyether is 2:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0075] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0076] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0077] Example 9

[0078] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 76% of polyether ester (6000), 10% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 14% of oleic acid.

[0079] The preparation method comprises the following steps:

[0080] (1) A difunctional polyether with a molecular weight of 6000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C, a reaction time of 4 hours, phosphorous acid as a catalyst, an addition amount of 3‰, a molar ratio of PIBSA:polyether of 2:1, and the reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0081] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0082] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0083] Example 10

[0084] The fully synthetic metalworking fluid composite lubricant of the invention comprises the following components in percentage by mass: 76% of polyether ester (4000), 14% of oleyl alcohol polyoxyethylene ether (10)-maleate, and 10% of oleic acid.

[0085] The preparation method comprises the following steps:

[0086] (1) A difunctional polyether with a molecular weight of 4000 and a molecular structure of EPE (PPG as an initiator and EO at the end) is esterified with PIBSA at a reaction temperature of 80°C-90°C for 4 hours. The catalyst is phosphorous acid in an amount of 3‰. The molar ratio of PIBSA to polyether is 2:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 450mL / min.

[0087] (2) The oleyl alcohol polyoxyethylene ether (10) is esterified with maleic anhydride at a reaction temperature of 80°C-90°C for 4 hours. No catalyst is required for the reaction. The molar ratio of oleyl alcohol polyoxyethylene ether (10): polyether is 1:1. The reaction needs to be carried out under the action of nitrogen blowing. Taking a 1000mL three-necked flask as an example, the nitrogen flow rate is 250mL / min. Before the reaction, vacuum and nitrogen filling are required to remove oxygen carried by maleic anhydride and polyether to prevent the material from turning red.

[0088] (3) Compounding oleic acid, PIBSA polyether ester and oleyl alcohol polyoxyethylene ether (10) maleate to obtain a fully synthetic metalworking fluid composite lubricant.

[0089] The performance of the fully synthetic metalworking fluid composite lubricant of Examples 1 to 7 was tested:

[0090] 1. Foam test:

[0091] 1. Add 10% of the sample in the test solution and stir to make the reaction even;

[0092] 2. Dilute 50 ml of each solution with tap water (water hardness 125 ppm) at a ratio of 5% and pour into a 100 ml stoppered measuring cylinder;

[0093] 3. Shake the stoppered measuring cylinder up and down 60 times at a frequency of 120 times / min. After standing, record the foam height and defoaming time.

[0094] 2. Thermal stability test:

[0095] The test solution samples and the example samples were placed in a 50°C constant temperature box and left to stand for 48 hours to observe whether there was precipitation, settling or turbidity. The results were judged as qualified if there was no precipitation, settling or turbidity.

[0096] Table 1. Foam performance and thermal stability test results of composite lubricants of Examples 1 to 10

[0097]

[0098]

[0099] As shown in Table 1, different composite lubricants were prepared in Examples 1 to 7 by adjusting the ratio of PIBSA polyether ester. It can be seen that the composite lubricants prepared in Examples 1 to 7 all meet the requirements of thermal storage stability. It can be observed that the foaming performance of polyether ester 6000 is greater than that of polyether ester 4000, and the greater the amount of polyether ester 6000 added, the higher the foam height and the slower the defoaming speed. It is speculated that the cause of this phenomenon is that on the one hand, polyether ester 6000 has stronger hydrophilicity, and cooperates with oleyl alcohol polyoxyethylene ether (10)-maleate to form the functions of foaming and stabilizing foam. On the other hand, polyether ester polyether ester 6000 has a larger molecular weight and more hydrogen bonds introduced into the EO segment, resulting in a larger microscopic viscosity of the system, a lower water-oil exchange rate in the foam, and better foam stabilizing performance.

[0100] The results of Examples 8-9 show that reducing the proportion of oleyl alcohol polyoxyethylene ether (10)-maleate and increasing the proportion of oleic acid will increase the defoaming speed of the system and reduce the initial foam. This is because the proportion of the modified dispersant oleyl alcohol polyoxyethylene ether (10)-maleate is reduced, which is conducive to soap precipitation. Similarly, increasing the soaping agent oleic acid can also achieve a similar effect. A large amount of soap precipitation will cause the solid soap to pierce the foam, improving the low-foaming performance of the product, but will reduce the hard water resistance of the product. The hard water resistance performance is shown in Table 3 and the hard water resistance test results of the composite lubricants of Examples 1 to 7

[0101] 3. Lubrication performance test (long wear test):

[0102] The test conditions are: 40 kg, 30 min, 1200 rpm, and starting temperature 40°C.

[0103] Table 2. Long wear test results of composite lubricants of Examples 1 to 10

[0104]

[0105]

[0106] As shown in Table 2 and Figure 1 As shown, it can be found from Examples 1-7 that the wear spot size increases with the increase in the proportion of polyether ester 4000, which reflects that the lubrication performance of the composite agent increases with the increase in the proportion of polyether ester 4000. This is because the lubrication performance of polyether ester is closely related to the alkane segments contained in the polyether ester. The intrinsic lubrication performance of polyether ester 4000 is better than that of polyether ester 6000. However, in actual applications, the price of polyether is much lower than that of PIBSA. Therefore, under certain cost constraints, polyether esters with higher polyether content have better cost performance.

[0107] 4. Hard water resistance test:

[0108] In the test plan, add the example sample at 10%, stir and react evenly; dilute the completely reacted test sample at 5% with 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, and 1000ppm hard water respectively, and let it stand for 24h; after standing for 24h, observe the appearance of the diluted solution to see if there is soap precipitation, precipitation and other phenomena; the result is judged as: if there is no soap precipitation and other phenomena, it is judged as passed, and if there is soap precipitation, it is judged as failed.

[0109] Table 3. Hard water resistance test results of composite lubricants of Examples 1 to 10

[0110] Example No. Hard water resistance level, ppm Example 1 800 Example 2 600 Example 3 600 Example 4 500 Example 5 500 Example 6 400 Example 7 400 Example 8 300 Example 9 200 Example 10 1000

[0111] As shown in Table 3, by comparing specific examples 1-7, it can be observed that the intrinsic hard water resistance of polyether ester 6000 and polyether ester 4000 is different. When the modified dispersant oleyl alcohol polyoxyethylene ether (10)-maleate and the soaping agent oleic acid are fixed, when polyether ester 6000 is replaced with an equal amount of polyether ester 4000, the hard water resistance decreases with the decrease in the addition amount. This may be due to the longer EO segment of polyether ester 6000. Compared with polyether ester 4000, it has a longer hydrophilic group auxiliary oleyl alcohol polyoxyethylene ether (10)-maleate. The present invention relates to polyol polyoxyethylene ether (10)-maleate (which has a similar structure and also has certain calcium soap dispersibility). However, it must be pointed out that the hard water resistance brought about by the calcium soap dispersibility is contrary to the foam performance. Under the same hard water concentration (such as 170ppm hardness of tap water), the product with higher hard water resistance has relatively higher foam. For example, in specific embodiment 10, when the concentration of oleyl alcohol polyoxyethylene ether (10)-maleate is further increased and the concentration of oleic acid is reduced, the foam of the product is not only slightly increased, but also the defoaming speed is greatly reduced.

[0112] 5. Iron filings anti-corrosion test:

[0113] Test method: 1. Add the embodiments into the test solution at a ratio of 10%, stir to react evenly, and prepare test samples; dilute with tap water (water hardness 125ppm) at a ratio of 5%, and test with iron filings anti-rust test method (IP287); Result judgment: no rust: level 0, several rust spots: level 1, dozens of rust spots: level 2, dozens of rust spots: level 3, severe rust: level 4.

[0114] Table 4. Iron chip anticorrosion test results of composite lubricants of Examples 1 to 10

[0115] Example No. Result determination Example 1 No rust, grade 0 Example 2 No rust, grade 0 Example 3 No rust, grade 0 Example 4 No rust, grade 0 Example 5 No rust, grade 0 Example 6 No rust, grade 0 Example 7 No rust, grade 0 Example 8 No rust, grade 0 Example 9 No rust, grade 0 Example 10 No rust, grade 0

[0116] As shown in Table 4 and Figure 2As shown, this type of product has good anti-rust performance. This is because, unlike polyether products, the main lubricant polyether ester, the modified dispersant oleyl alcohol polyoxyethylene ether (10)-maleate and the soaping agent oleic acid of this product all have a strongly polar anionic carboxylic acid structure, which ionizes in the amine cutting fluid to form carboxylate anions, which can form a strong adsorption film on the metal surface. It has a certain hydrophobicity. This competitive adsorption can dilute and reduce the adsorption of corrosive media and metal surfaces, so it has good anti-rust performance.

Claims

1. A fully synthetic metalworking fluid composite lubricant, characterized in that: The composite lubricant comprises the following components in percentage by mass: 76% of a main lubricant, 10-14% of a dispersant, and 10-14% of a soaping agent; wherein the main lubricant is polyisobutylene succinic anhydride-polyether ester, the dispersant is oleyl alcohol polyoxyethylene ether 10-maleate, and the soaping agent is oleic acid.

2. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The polyisobutylene succinic anhydride-polyether ester is a polyisobutylene succinic anhydride ester of polyether ester 4000 or polyether ester 6000.

3. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: In the polyisobutylene succinic anhydride-polyether ester, both ends of the molecular structure of the polyether ester are terminated with polyisobutylene succinic anhydride carboxyl groups, the carboxyl groups of the polyisobutylene succinic anhydride react with the polyether to form an ester bond, and the center of the molecular structure is a polyether structure.

4. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The preparation method of the main lubricant is to carry out esterification reaction of difunctional polyether and polyisobutylene succinic anhydride, the reaction temperature is 80°C-90°C, the reaction time is 4-8 hours, the catalyst is phosphorous acid, the addition amount is 1.5-3‰, the molar ratio of polyisobutylene succinic anhydride to difunctional polyether is 1.85-2.25:1, and the reaction is carried out under the action of nitrogen blowing to obtain the main lubricant.

5. The fully synthetic metalworking fluid composite lubricant according to claim 4, characterized in that: The difunctional polyether has an EO-PO mass ratio of 8:2, a molecular weight of 4000-6000, and a molar ratio of polyisobutylene succinic anhydride to the difunctional polyether of 1.85-2.25:

1.

6. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The oleyl alcohol polyoxyethylene ether 10-maleate is an ester with a carboxyl terminal structure.

7. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The preparation method of oleyl alcohol polyoxyethylene ether 10-maleate is as follows: esterify oleyl alcohol polyoxyethylene ether 10 with maleic anhydride, with a heating rate of 5-10°C / min, a reaction temperature of 80°C-90°C, and nitrogen blowing at a nitrogen flow rate of 250-450mL / min.

8. The fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The oleic acid is an unsaturated acid.

9. A method for preparing the fully synthetic metalworking fluid composite lubricant according to claim 1, characterized in that: The preparation method is: (1) preparing a main lubricant polyisobutylene succinic anhydride-polyether ester; (2) preparing dispersant oleyl alcohol polyoxyethylene ether 10-maleate; (3) The product is prepared by compounding oleic acid, polyisobutylene succinic anhydride-polyether ester and oleyl alcohol polyoxyethylene ether 10-maleate.

10. Use of the fully synthetic metalworking fluid composite lubricant according to claim 1 in the field of metalworking.